Modelling physiological complexity: Dynamic integration of the neuromuscular system during quasi-static exercises performed until failure - Balague, N.; Hristovski, R. (Sportinformatik gestern, heute morgen. Festschrift zu Ehren von Prof. Jürgen Perl, 2010)
Attempting to explain the maximum number of phenomena using a minimum num-ber of independent principles is a long-standing aim of the scientific endeavour. The formation of general theories has always been accompanied by the art of modelling the phenomena of interest within the general framework of theories, the aim being to corroborate or falsify their inner theoretical structure by testing the model's predictions. In other words, models may be seen as applications of general theoretical principles to specific Systems and phenomena.